Pengaruh Isi Pekerjaan dan Kepuasan Kerja Terhadap Kinerja Karyawan Di Hotel “Armani” Muara Teweh Kalimantan Tengah - Rusanita Rusanita; Emy Rahmawati; Setio Utomo (Universitas Lambung Mangkurat, 2019)
The existence of inpatient services as a means of supporting business and industry in Muara Teweh North Barito Regency has progressed. Hotels in Muara Teweh North Barito Regency as many as 4 units, Hotel Armani Muara Teweh is the first hotel with starred facilities. With the existence of Armani hotel is able to help assist in terms of taxation, local employment and support in the world of tourism so as to facilitate the investors / businessmen to come to the town of Muara Teweh Central Kalimantan. This study aimed to examine the effect of Content Works (X1) and Job Satisfaction (X 2) the Employee Performance (Y) in